2016
DOI: 10.1111/hdi.12414
|View full text |Cite
|
Sign up to set email alerts
|

Reduced protein bound uraemic toxins in vegetarian kidney failure patients treated by haemodiafiltration

Abstract: Introduction Indoxyl sulfate (IS) and p cresyl sulfate (PCS) are protein bound toxins which accumulate with chronic kidney disease. Haemodiafiltration (HDF) increases middle molecule clearances and has been suggested to increase IS and PCS clearance. We therefore wished to establish whether higher convective clearances with HDF would reduce IS and PCS concentrations. Methods We measured total plasma IS and PCS in a cohort of 138 CKD5d patients treated by On-line HDF (Ol-HDF), by high pressure liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 33 publications
0
61
0
2
Order By: Relevance
“…Patients eating vegetarian diets have been reported to have lower SAF (26), and also lower circulating protein-bound azotemic toxins (27). Patients eating vegetarian diets have been reported to have lower SAF (26), and also lower circulating protein-bound azotemic toxins (27).…”
Section: Discussionmentioning
confidence: 99%
“…Patients eating vegetarian diets have been reported to have lower SAF (26), and also lower circulating protein-bound azotemic toxins (27). Patients eating vegetarian diets have been reported to have lower SAF (26), and also lower circulating protein-bound azotemic toxins (27).…”
Section: Discussionmentioning
confidence: 99%
“…In vegetarian patients undergoing hemodiafiltration (HDF), the levels of indoxyl sulfate (IS) and p cresyl sulfate (PCS) (protein bound toxins that accumulate in CKD) were also demonstrated to be lower [75]. The authors suggested that a vegetarian diet might potentially reduce IS and PCS production by the intestinal microbiome.…”
Section: Other Effectsmentioning
confidence: 99%
“…P-cresylsulphate has similarly been linked to CKD and CVD mortality, although the mechanism is not as well defined [44,45]. Interestingly, it has been noted that vegetarians have lower levels of these nephrotoxic compounds compared with omnivores, in both healthy [46] and CKD populations [47]. Vegetarians tend to have higher fibre intakes [46], which could be metabolized by the colonic microbiota instead of amino acids, leading to a reduction in indoxyl sulphate and p-cresylsulphate.…”
Section: Proteinmentioning
confidence: 99%